Pengaruh Stres Kerja Dan Motivasi Kerja Terhadap Kinerja Pelaku Umkm Di Wilayah Sampang Madura Jawa Timur - Riski, Riski; Basalamah, Muhammad Ridwan; Arsyianto, Muhammad Tody (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research was conducted to determine the effect of work stress and work motivation on the performance of MSME actors in the Tlagah village area, sub-district. Banyuates district. Sampang, Madura, East Java. The type of research used is quantitative research. The sample in this research amounted to 63 respondents with the technique used in this research being non-probability sampling. The research results show that the results of the f test for work stress and work motivation simultaneously have a significant effect on the performance of MSME actors. From the results of the t-test analysis, it is known that the work stress variable has a significant effect on the performance of MSME actors, the work motivation variable has a significant effect on the performance of MSME actors. Keywords: Work stress, work motivation and performance of MSME actors